2020
DOI: 10.2217/hep-2020-0004
|View full text |Cite
|
Sign up to set email alerts
|

Systemic treatment of hepatocellular carcinoma: from sorafenib to combination therapies

Abstract: For almost a decade, systemic therapy of advanced hepatocellular carcinoma (HCC) was limited to the tyrosine kinase inhibitor (TKI) sorafenib. Different agents including checkpoint inhibitors, TKIs and anti-VEGFR antibodies demonstrated efficacy in treatment. For the first time, the combination of atezolizumab and bevacizumab, a first-line treatment that is superior to the current standard was identified, potentially changing the way we treat HCC. In this review, we summarize current data on systemic treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 54 publications
(60 reference statements)
0
27
0
4
Order By: Relevance
“…Although ICIs showed limited efficacy as single agents, combined therapies have revolutionized the treatment regimens of advanced HCC. 108 Importantly, HCC does not respond to classical cytotoxic chemotherapy. Different mechanisms of resistance to chemotherapy have been proposed, such as reduced drug uptake and increased drug efflux/metabolism, increased DNA repair mechanisms, decreased DNA-damage-induced cell-cycle arrest, impaired apoptosis and enhanced survival pathways (e.g., phosphatidylinositol 3-kinase [PI3K]/AKT/ mTOR), activation of autophagy, and deregulation of the epigenetic machinery to promote stem cell epigenetic signatures.…”
Section: Systemic Therapies For Advanced Hccmentioning
confidence: 99%
“…Although ICIs showed limited efficacy as single agents, combined therapies have revolutionized the treatment regimens of advanced HCC. 108 Importantly, HCC does not respond to classical cytotoxic chemotherapy. Different mechanisms of resistance to chemotherapy have been proposed, such as reduced drug uptake and increased drug efflux/metabolism, increased DNA repair mechanisms, decreased DNA-damage-induced cell-cycle arrest, impaired apoptosis and enhanced survival pathways (e.g., phosphatidylinositol 3-kinase [PI3K]/AKT/ mTOR), activation of autophagy, and deregulation of the epigenetic machinery to promote stem cell epigenetic signatures.…”
Section: Systemic Therapies For Advanced Hccmentioning
confidence: 99%
“…However, the study was recently halted after the completion of an interim futility analysis [ 155 ]. Further studies employing other therapeutic agents, combinations of treatments and adjuvants and in different stages of disease are on the way (e.g., NCT03203005 and NCT03071094) [ 156 ].…”
Section: Immunological Therapeutic Approachesmentioning
confidence: 99%
“…Most recently, it was demonstrated that patients with PD-L1 positive gastric cancer show improved response rates and improved survival compared to patients without PD-L1 expression [ 19 ]. While the same was true, e.g., for patients with non-small cell lung cancer [ 20 ], PD-L1 tumor expression was neither predictive nor prognostic in other tumor entities such as hepatocellular carcinoma (HCC) [ 21 ]. In terms of circulating biomarkers for ICI therapy, data are scarce; some authors have suggested that serum lactate dehydrogenase (LDH) levels [ 22 , 23 ] and the neutrophil/lymphocyte ratio (NLR) might correlate with an unfavorable prognosis in patients with melanoma and/or NSCLC treated with ICI.…”
Section: Discussionmentioning
confidence: 99%